An Empirical Study on Stress Coping Strategies among the Employees in Information Technology Sector - M. Aravinda (Modern Perspectives in Economics, Business and Management Vol. 5, 2021)
Stress is a physical, mental, and emotional reaction that occurs as a result of an individual’s reaction to environmental pressure. The stress coping mechanisms of employees in the Information Technology sector are investigated in this paper. This study addresses the numerous elements that create stress among IT sector employees, as well as the various coping mechanisms used by IT sector employees to manage stress and preserve work-life balance during their employment. For this study, a descriptive research design was used, and both primary and secondary data were used to derive results. The sample size for this study was set at 120 people, with respondents chosen from four different IT organizations in the Hyderabad area. The data was gathered using a structured questionnaire, and statistical analysis was carried out using the Chi-square test and ANOVA. The result revealed that there is a significant mean difference between the respondents’ age factor and the stress coping strategies they use to balance their work life.